Pelaksanaan Pembelajaran SMP Ta’mirul Islam Surakarta di Masa Pandemi Covid-19 - Ainun Yudhistira (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2021)
The COVID-19 pandemic that occurred in 2020 has changed all aspects of human life today, especially in the field of education. This requires all elements of education from lower to upper levels to adapt so that the learning process can still be carried out. The purpose of this paper is to provide an overview of the implementation of learning during the COVID-19 pandemic.